INVESTIGATING STUDENTS' NEEDS FOR THE WEEKLY ENGLISH PROGRAM AT MUHAMMADIYAH BOARDING SCHOOL PALOPO: A CASE STUDY (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
One of the flagship programs at Muhammadiyah Boarding School is the English Language development program known as the Weekly English program. This study aimed to identify the needs of students at Muhammadiyah Boarding School in Palopo. The descriptive qualitative approach was used in this study. The study included 27 students as participants. The researchers interviewed teachers and students during the weekly English program to learn more about their needs and perspectives. According to the findings of the researchers' observations and interviews with teachers and students, an appropriate module is needed as one of the learning resources in the Weekly English program. It is needed to provide the materials and exercises given in one level during the program at Muhammadiyah Boarding School.
Keywords: English Language Development; Module; Weekly English